If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + k + -3 = 3 Reorder the terms: 5 + -3 + k = 3 Combine like terms: 5 + -3 = 2 2 + k = 3 Solving 2 + k = 3 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + k = 3 + -2 Combine like terms: 2 + -2 = 0 0 + k = 3 + -2 k = 3 + -2 Combine like terms: 3 + -2 = 1 k = 1 Simplifying k = 1
| 1x(8-x)=8-x | | 205-v=158 | | M-48=87 | | X-50=-25 | | 20x+45=225 | | 1l(8-x)=8-x | | 6w+8=48 | | q/3=31/1 | | 74=28+V | | 4j/12=-1 | | 72-w=8w | | y=rx+3 | | 13b=78 | | X-4=-9-4x | | 5n-2-7n=-14 | | 4x-18=3(2x-9) | | 7-2n=-13-6n | | 7.50p+2.50=12.50 | | 8x+3+4(x-5)= | | 5(r-5)-4(r-1)=2(r+4) | | 2M/(22M^2) | | 3x-2(4x-3)=6-(x+8) | | -7y+3=-22 | | y+2*-4=-6 | | 8w=27+5w | | 9x-2b+8b+3x= | | 3(4x+1)-2(2x-7)=73 | | 70-(3Q+70)=70-4Q | | 4x+5x-2=16 | | 4.5+y=y-5.5 | | 16x+17=73 | | X-(-2-x)=-2(-2x-4) |